2007
DOI: 10.1021/ma0713714
|View full text |Cite
|
Sign up to set email alerts
|

Highly Refractive and Transparent Polyimides Derived from 4,4‘-[m-Sulfonylbis(phenylenesulfanyl)]diphthalic Anhydride and Various Sulfur-Containing Aromatic Diamines

Abstract: We have developed highly refractive and transparent polyimides (PIs). The PIs were prepared from a newly developed meta-substituted sulfonyl-bridged dianhydride, 4,4′-[m-sulfonylbis(phenylenesulfanyl)]diphthalic anhydride (DPSDA), and various sulfur-containing aromatic diamines, including 4,4′-thiobis [(pphenylenesulfanyl)aniline] (3SDA), 4,4′-sulfonylbis[(p-phenylenesulfanyl)aniline] (BADPS), 2,8-bis(p-aminophenylenesulfanyl)dibenzothiophene (APDBT), and 2,7-bis(p-aminophenylenesulfanyl)thianthrene (APTT), by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
99
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 38 publications
(57 reference statements)
1
99
0
Order By: Relevance
“…[22][23][24][25][26] It was proved that these copolymer networks are electrochemically active and can be used in cathodes of Li-S batteries with enhanced charge capacity and lifetime (1000 mA h g 21 and 500 charge-discharge cycles were measured with the produced batteries). [22][23][24][25][26] Moreover, it was showed that these sulfur-rich copolymer networks present interesting properties as high refractive index polymers (HRIP) [22][23][24]27 with important applications in advanced optoelectronic fabrications (e.g., advanced displays, OLEDs, and antireflective coatings [28][29][30] ). The design of copolymer network composition (through the initial S/crosslinker ratio) is an important issue in order to tailor the properties of the final materials.…”
mentioning
confidence: 99%
“…[22][23][24][25][26] It was proved that these copolymer networks are electrochemically active and can be used in cathodes of Li-S batteries with enhanced charge capacity and lifetime (1000 mA h g 21 and 500 charge-discharge cycles were measured with the produced batteries). [22][23][24][25][26] Moreover, it was showed that these sulfur-rich copolymer networks present interesting properties as high refractive index polymers (HRIP) [22][23][24]27 with important applications in advanced optoelectronic fabrications (e.g., advanced displays, OLEDs, and antireflective coatings [28][29][30] ). The design of copolymer network composition (through the initial S/crosslinker ratio) is an important issue in order to tailor the properties of the final materials.…”
mentioning
confidence: 99%
“…These systematic decreases are essentially attributable to the lower polarizability per unit volume of sulfonyl linkage than that of -S-linkage. As discussed in our previous report, 11 the two oxygen atoms in sulfonyl linkage significantly increase the molecular volume of the linkage and reduce the content of polarizable sulfur atoms in the PIs. In addition, sulfonyl linkage renders reduction of the intermolecular CTC formation and the electron-donating ability of the diamine.…”
Section: Optical Properties Of Pismentioning
confidence: 51%
“…10 To remedy this problem, we reported highly refractive and transparent PIs derived from 4,4 0 -[m-sulfonylbis(phenylenesulfanyl)]diphthalic anhydride (mDPSDA) and various sulfurcontaining aromatic diamines. 11 The average refractive index (n av ) measured at 632.8 nm range from 1.7162 to 1.7432 depending on the different sulfur contents of PIs, and the metasubstituted electron-withdrawing sulfonyl moiety endowed PI films with good optical transparency. The optical transmittances of the PI films at 450 nm are higher than 85% for the thickness of ca.…”
mentioning
confidence: 99%
“…The sulfone materials have been applied to various high-performance engineering materials, such as fuel cell membranes, [17][18][19] gas separation membranes, 20,21 optical or photo materials, 22,23 etc. Because of the sulfonyl materials incorporated with the polymer materials, which could improve the thermal and oxidative stability, chemical resistance, and the glass transition temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%